Detection of Clinically Relevant Pain Relief in Cats with Degenerative Joint Disease Associated Pain. (10th February 2014) - Gruen, M.E.; Griffith, E.; Thomson, A.; Simpson, W.; Lascelles, B.D.X.
<x xml:space="preserve">Abstract</x> Background Detection of clinically relevant pain relief in cats with degenerative joint disease (DJD) is complicated by a lack of validated outcome measures and a placebo effect. Hypothesis/Objectives To evaluate a novel approach for detection of pain relief in cats with DJD. Animals Fifty‐eight client‐owned cats. Methods Prospective, double‐masked, placebo‐controlled, stratified, randomized, clinical study. Enrolled cats were 6–21 years of age, with owner‐observed mobility impairment, evidence of pain in at least 2 joints during orthopedic examination, and overlapping radiographic evidence of DJD, and underwent a 2‐week baseline period, 3‐week treatment period with placebo or meloxicam, and 3‐week masked washout period. Outcome measures were evaluated at days 0, 15, 36, and 57. Results Both groups significantly improved after the treatment period (day 36) on client‐specific outcome measures (CSOM) and feline musculoskeletal pain index (FMPI) (P < .0001 for both); there was no difference between the groups on CSOM or FMPI score improvement. After the masked washout period, more cats that received meloxicam during the treatment period had a clinically relevant decrease in CSOM score (P = .048) and FMPI score (P = .021) than cats that received placebo. Conclusions and Clinical Importance Using both a client‐specific and a general clinical metrology instrument, owners of cats with DJD were able to detect evident recurrence of clinical signs after withdrawal of active medication than after withdrawal of placebo, and that this study design might be a novel and useful way to circumvent the placebo effect and detect the efficacy of pain‐relieving medications.